2013
DOI: 10.5898/jhri.2.3.moon
|View full text |Cite
|
Sign up to set email alerts
|

Design and Impact of Hesitation Gestures during Human-Robot Resource Conflicts

Abstract: In collaborative tasks, people often communicate using nonverbal gestures to coordinate actions. When two people reach for the same object at the same time, they often respond to an imminent potential collision with jerky halting hand motions that we term hesitation gestures. Successful implementation of such communicative conflict response behaviour onto robots can be useful. In a myriad of human-robot interaction contexts involving shared spaces and objects, this behaviour can provide a fast and effective me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Similar to the presented study, Moon et al [36] found less evidence in objective measures like human performance than in subjective measures, where participants regarded the movements as hesitations. The authors did not find sufficient evidence that the hesitation motion profile improved human-robot task completion time, while results suggested that participants can recognize such robot responses as hesitations and distinguished them from abrupt stopping behaviours.…”
Section: Implications Of the Video Studysupporting
confidence: 84%
“…Similar to the presented study, Moon et al [36] found less evidence in objective measures like human performance than in subjective measures, where participants regarded the movements as hesitations. The authors did not find sufficient evidence that the hesitation motion profile improved human-robot task completion time, while results suggested that participants can recognize such robot responses as hesitations and distinguished them from abrupt stopping behaviours.…”
Section: Implications Of the Video Studysupporting
confidence: 84%
“…Studies have shown clear correlations between musical features and movement features, suggesting that a single model can be used to express emotion through both music and movement [31], [32], [33]. Certain characteristics of robotic motion have been shown to influence human emotional response [34], [35]. Additionally, emotional intelligence in robots leads to facilitated human-robot interactions [36], [25], [37].…”
Section: Emotion Music and Gesturementioning
confidence: 99%
“…After each block and at the experiments' end, participants answered questions about their impressions of the robot, collaborative quality, and method comparisons ( Table 2). Parts of the questionnaire were adapted from Bartneck, Kulić, Croft, & Zoghbi (2008) and Moon, Parker, Croft, & Van der Loos (2013).…”
Section: Metricsmentioning
confidence: 99%